The lived experiences of school lunch: an empathy-based study with children in Sweden - L. Berggren; C. Olsson; S. Talvia; A. Hörnell; M. Rönnlund; M. Waling (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
School lunch is in general regulated through policies and agendas constituted by the perspectives of adults. In this article, we focus on children's lived experiences of school lunch with a special emphasis on emotions and how they relate to social and physical dimensions. This study draws on empathy-based stories written by 10-11 year olds (n = 171) from schools in Sweden. We identified three themes: Interaction and exposure, Routines and restrictions and Food and eating. The children's lived experiences of school lunch and the emotions attached to them are closely associated and intertwined with the socio-spatial dimension of school lunch. A pleasant meal experience seems to require harmonization between the physical and social space whilst negative experiences contain tensions between them, something that actors working with school lunch and school lunch environments should take in consideration when resourcing, planning and scheduling school lunch, and also when designing new school restaurants.